Fn14-targeted BiTE and CAR-T cells demonstrate potent preclinical activity against glioblastoma. (1st January 2021) - Li, Gaowei; Zhang, Zongliang; Cai, Linjun; Tang, Xin; Huang, Jianhan; Yu, Lingyu; Wang, Guoqing; Zhong, Kunhong; Cao, Yi; Liu, Chang; Wang, Yuelong; Tong, Aiping; et al.
ABSTRACT: T cell-engaging therapies involving bispecific T cell engager (BiTE) and chimeric antigen receptor T (CAR-T) cells have achieved great success in the treatment of hematological tumors. However, the paucity of ideal cell surface molecules that can be targeted on glioblastoma (GBM) partially reduces the immunotherapeutic efficacy. Recently, high expression of Fn14 has been reported in several solid tumors, so the strategy of exploiting this specific antigen for GBM immunotherapy is worth studying. Consequently, we constructed Fn14× CD3 BiTE and Fn14-specific CAR-T cells and investigated their cytotoxic activity against GBM in vitro and in vivo. First, expression of Fn14 was confirmed in glioma tissues and GBM cells. Then, we designed Fn14-specific BiTE and CAR-T cells and tested their cytotoxicity in GBM cell cultures and mouse models of GBM. Fn14 was highly expressed in GBM tissues and cell lines, while it was undetectable in normal brain samples. Fn14× CD3 BiTE, Fn14 CAR-T cells and Fn14 CAR-T/IL-15 cells were antigen-specific and highly cytotoxic, showing good antitumor activity in vitro and causing significant regression of established solid tumors in xenograft models. However, the xenografts treated with Fn14 CAR-T cells regrew, whereas xenografts treated with Fn14 CAR-T/IL-15 cells did not. IL-15 engineering augmented the antitumor activity of Fn14 CAR-T cells and resulted in significant antitumor effects similar to those of Fn14× CD3 BiTE. Our results suggest that Fn14 is an appropriate target for GBM. Anti-Fn14 BiTE and Fn14-specific CAR-T/IL-15 cells may be exciting immunotherapeutic options for malignant brain cancer.